The Relationship of Sustainability Report, Corporate Risk, and Transfer Pricing on Tax Avoidance - Kyla Naomi Lesmana; Marthinus Ismail; Lenita Waty (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Taxes serve as the largest source of state revenue, making them a crucial instrument in national development. Tax avoidance through various strategies results in significant losses for the state. Therefore, this study aims to provide a new perspective on the relationship between the Sustainability Report, Corporate Risk, and Transfer Pricing towards tax avoidance practices. This research employs a quantitative approach with a sample of 19 energy companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2023 period. The findings indicate that disclosure in the Sustainability Report and Corporate Risk does not affect tax avoidance, whereas Transfer Pricing has a significant impact on tax avoidance practices among energy companies. Simultaneously, the Sustainability Report, Corporate Risk, and Transfer Pricing do not have a significant effect on Tax Avoidance.